2015
DOI: 10.1080/15287394.2015.1085355
|View full text |Cite
|
Sign up to set email alerts
|

Negligible Pharmacokinetic Interaction of Red Ginseng and Losartan, an Antihypertensive Agent, in Sprague-Dawley Rats

Abstract: Red ginseng (RG) is one of the top selling herbal medicines in Korea, but is not recommended in hypertensive patients. In this study, the pharmacokinetic (PK) interaction between RG and losartan, an antihypertensive drug, was examined. RG was orally administered for 2 wk to male Sprague-Dawley (S-D) rats at either control (0), 0.5, 1, or 2 g/kg/d for 2 wk. After the last administration of RG and 30 min later, all animals were treated with 10 mg/kg losartan by oral route. In addition, some S-D rats were adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Only amlodipine exhibited a delayed Tmax following multiple red ginseng extract administrations, and this was attributed to altered absorption kinetics due to decreased intestinal permeability [ 75 ]. Several animal studies indicated that red ginseng has minimal impact on the pharmacokinetics of amlodipine, as well as on that of losartan and its active metabolite EXP-3174, in rats [ 76 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only amlodipine exhibited a delayed Tmax following multiple red ginseng extract administrations, and this was attributed to altered absorption kinetics due to decreased intestinal permeability [ 75 ]. Several animal studies indicated that red ginseng has minimal impact on the pharmacokinetics of amlodipine, as well as on that of losartan and its active metabolite EXP-3174, in rats [ 76 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…The use of natural products with therapeutic properties is as old as human civilization, and for a long time, minerals, plants, and animal products were the main sources of drug production (Rates, 2001;Santos et al, 2014;Maistro et al, 2015). Despite recent strides in modern medicine, plants still provide an important contribution to health (Calixto, 2000;Ryu et al, 2014). However, even though natural products are used extensively by the general population, many medicinal plants have not been subjected to rigorous scientific testing, and their properties are extremely variable (Capasso et al, 2000).…”
mentioning
confidence: 99%